1999
DOI: 10.7901/2169-3358-1999-1-485
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Nitrogen Concentration Supporting Maximum Crude Oil Biodegradation in Microcosms

Abstract: The purpose of this study was to determine the minimum nitrogen concentration needed by microorganisms to biodegrade crude oil hydrocarbons attached to sand particles in a microcosm simulating a low energy marine beach. The experimental approach involved mixing clean sand with weathered Alaska North Slope crude oil and monitoring biodegradation in continuous-flow beach microcosms over a 40-day time period. Two experiments were conducted with different nitrate-N concentrations in the feed (0, 0.25, 0.5, 1.0, 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Our results showed that the nitrogen concentrations observed in the beach were an order of magnitude lower than the optimum concentration (2 to 10 mg L −1 ) for biodegradation of oil hydrocarbons (Venosa et al 1996;Du et al 1999;Zhu et al 2001). Also our study showed that although the N:P ratio in the beach was greater than the optimum N:P ratio for oil biodegradation (around N:P = 10) (Liebeg and Cutright 1999), the concentrations of nitrogen and phosphate were an order magnitude lower than the recommended levels for biodegradation, suggesting that both nitrogen and phosphate are limiting biodegradation.…”
Section: Discussionmentioning
confidence: 48%
“…Our results showed that the nitrogen concentrations observed in the beach were an order of magnitude lower than the optimum concentration (2 to 10 mg L −1 ) for biodegradation of oil hydrocarbons (Venosa et al 1996;Du et al 1999;Zhu et al 2001). Also our study showed that although the N:P ratio in the beach was greater than the optimum N:P ratio for oil biodegradation (around N:P = 10) (Liebeg and Cutright 1999), the concentrations of nitrogen and phosphate were an order magnitude lower than the recommended levels for biodegradation, suggesting that both nitrogen and phosphate are limiting biodegradation.…”
Section: Discussionmentioning
confidence: 48%
“…This led to a major effort where around 55 tons of nutrients were applied on beaches of PWS (Bragg et al 1994). A recent study (Eslinger et al 2001) found that the maximum concentration of nutrient in PWS is less than 0.20 mg‐N/L, an order of magnitude smaller than the minimum needed for optimal (70%) biodegradation of hydrocarbons (Boufadel et al 1999; Du et al 1999; Zhu et al 2001).…”
Section: Introductionmentioning
confidence: 98%
“…A more recent study by Atlas and Bragg (2009) on the beach under study in this article found an average nutrient concentration of 0.24 mg N/L. Therefore, the nutrient nitrogen concentration is an order of magnitude smaller than the minimum needed for optimal biodegradation of hydrocarbons, which ranges from 2.0 to 10 mg/L (Boufadel et al 1999; Du et al 1999; Zhu et al 2001).…”
Section: Introductionmentioning
confidence: 64%